NILAI PENDIDIKAN KARAKTER KEARIFAN LOKAL TEMBANG BALI - Ni Wayan Aryani (LP3M Universitas PGRI Mahadewa Indonesia, 2020)
ABSTRACT In learning Balinese song, there are types of traditional and modern Balinese songs. Traditional Balinese songs include: (1) gegendingan (gending raré, gending jangér, gending sangiang), (2) sekar macapat or sekar alit such as pupuh-pupuh, (3) sekar madia such as kidung, and (4) sekar agung such as wirama. While what is called modern Balinese song in this paper are Balinese pop songs. Local wisdom recorded in Balinese songs is important to be explored, studied, and understood so that it can be used as guidelines to behave by the young generation of this nation, especially the young generation of Bali. Therefore, the treasures of local Balinese culture in the form of traditional song such as pupuh as well as modern Balinese pop songs are important sources of study for character education. Based on the cursory observations of Balinese song, especially Balinese pupuh and songs, it can be concluded that Balinese songs, both traditional and modern, are full of character education content which is certainly beneficial to foster the character and identity of young generation of Bali (in particular) and Indonesia (in general).